1988
DOI: 10.1017/s095026880005442x
|View full text |Cite
|
Sign up to set email alerts
|

Maternally derived measles immunity in children of naturally infected and vaccinated mothers

Abstract: SUMMARYMeasles antibody titres were established in three groups of infants: children of vaccinated mothers, children of unvaccinated mothers and neonates born after different gestational periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 9 publications
2
15
0
2
Order By: Relevance
“…In the USA, Sato and colleagues, [18] showed that the antibody level in the child decays exponentially from birth to 0 1 % of the cord value at age 11 months, which is consistent with our results (Table 2) if the critical HI dilution titre is 8. Mother and cord blood antibody levels tend to be lower in vaccinated mothers than motheis who had natural measles [19][20][21]; consequently, in highly vaccinated populations, the age at which most infants become susceptible may often be closer to that in developing countries. Chui and colleagues [22] present data from a small study in Alberta, Canada, showing that after 6 months, 93 % of the children of vaccinated mothers were without detectable neutralizing antibody (NT titre < 10), which would also be consistent with results from the Kenyan study if the critical HI dilution titre is 8.…”
Section: Decay Of Maternal Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, Sato and colleagues, [18] showed that the antibody level in the child decays exponentially from birth to 0 1 % of the cord value at age 11 months, which is consistent with our results (Table 2) if the critical HI dilution titre is 8. Mother and cord blood antibody levels tend to be lower in vaccinated mothers than motheis who had natural measles [19][20][21]; consequently, in highly vaccinated populations, the age at which most infants become susceptible may often be closer to that in developing countries. Chui and colleagues [22] present data from a small study in Alberta, Canada, showing that after 6 months, 93 % of the children of vaccinated mothers were without detectable neutralizing antibody (NT titre < 10), which would also be consistent with results from the Kenyan study if the critical HI dilution titre is 8.…”
Section: Decay Of Maternal Antibodymentioning
confidence: 99%
“…(17) In the particular case of order statistics the covariance matrix has the following structure (illustrating the result for four points): /a1ib al b2 al b3 al b4 = al b2 a2b2 a2b3 a2b4 ( a1 b3 a2 b3 a3 b3 a3 b4 al b4 a2b4 a3b4 a4 b4 where a = -nf(x) (19) (= I-)/Vnf(x). (20) The matrix V can be inverted analytically to obtain U = V-1. U is tridiagonal so that we may write and it is straightforward to show that bn_l an+l-an-l bn+l (22) (bnlan-an-l bn) (bn a -a b(2+2)) (25) from which it follows that k1_ l'Ul = E (ax + 2fis) (26) k2l1'Uz = E (aj Zi + fli(Zi + zj+ )) (27) z'U1 = (l'Uz)' = k2 (28) …”
Section: Appendix Imentioning
confidence: 99%
“…[9][10][11][12] and infants born to vaccinated mothers acquire a lower level of measles antibody, which disappears at an earlier age, than infants born to mothers who have had natural measles infection . Therefore, children born to vaccinated mothers may be vulnerable to natural measles infection and be able to respond to measles vaccine at a younger age than infants of unvaccinated mothers [9,10,[12][13][14][15][16][17]. In the future, as the proportion of mothers who have been vaccinated increases, it may be possible to reduce the recommended age of measles vaccine, for all or for selected groups of children [9,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, children born to vaccinated mothers may be vulnerable to natural measles infection and be able to respond to measles vaccine at a younger age than infants of unvaccinated mothers [9,10,[12][13][14][15][16][17]. In the future, as the proportion of mothers who have been vaccinated increases, it may be possible to reduce the recommended age of measles vaccine, for all or for selected groups of children [9,10,[12][13][14]. The aim of this study was to provide data which would assist in identifying the optimum age for vaccinating UK children in the future.…”
Section: Introductionmentioning
confidence: 99%
“…15 Several other vaccine studies also indicate that maternal antibodies in the offspring of naturally immune are more potent than vaccinated women e.g. vaccinating women with live attenuated measles vaccine offered shorter term protection against measles to their children than naturally infected mothers, [16][17][18] suggest generation of higher avidity antibodies after infection than after vaccination. Such antibody, although low in concentration, can bind pertussis vaccine antigen more effectively to promote opsonophagocytosis and enhance clearance by macrophages and neutrophils.…”
Section: Discussionmentioning
confidence: 99%